What Does MFN Trade Mean for India and Pakistan? Can MFN be a Panacea? - De, Prabir (World Bank, Washington, DC, 2013)
India and Pakistan, the two largest economies in South Asia, share a common border, culture and history. Despite the benefits of proximity, the two neighbors have barely traded with each other. In 2011, trade with Pakistan accounted for less than half a percent of India's total trade, whereas Pakistan's trade with India was 5.4 percent of its total trade. However, the recent thaw in India-Pakistan trade relations could signal a change. Pakistan has agreed to grant most favored nation status to India. India has already granted most favored nation status to Pakistan. What will be the gains from trade for the two countries? Will they be inclusive? Is most favored nation status a panacea? Should the granting of most favored nation status be accompanied by improvements in trade facilitation, infrastructure, connectivity, and logistics to reap the true benefits of trade and to promote shared prosperity? This paper attempts to answer these questions. It examines alternative scenarios on the gains from trade and it finds that what makes most favored nation status work is the trade facilitation that surrounds it. The results of the general equilibrium simulation indicate Pakistan's most favored nation status to India would generate larger benefits if it were supported by improved connectivity and trade facilitation measures. In other words, gains from trade would be small in the absence of improved connectivity and trade facilitation. The idea of trade facilitation is simple: implement measures to reduce the cost of trading across borders by improving infrastructure, institutions, services, policies, procedures, and market-oriented regulatory systems. The returns can be huge, even with modest resources and limited capacity. The dividends of trade facilitation can be shared by all.